A Study on Health Experiences of the Social Classes in Terms of Drugs - Hatice Özer (İnsan & Toplum)
This study examines the methods of healthcare experiments of the social classes specific to the prescription of “original” and “generic” drug forms that are at the center of Turkey’s recent healthcare policies. In Turkey, the promotion of generic drug production began after the 2000s in line with certain social and economic objectives. As generic drugs do not require a long, costly R&D process this not only offers an advantage for the state in terms of drug purchasing, but was also coded as a “local” drug form that would reduce the risks of foreign dependency. After the generically produced, original drugs were added to the reimbursement list, marketing activities in the field of producing generic drugs increased. The study aims to examine the association in the consumption aspect in the production field of these drugs developed according to the usage value based on notes taken in interviews with a total of 16 doctors in Bağcılar, Istanbul where doctor visits by generic drug companies established with local capital became more concentrated. The doctors in question said the pharmaceutical promotion representatives influenced their choice of brands; the generic drug manufacturing companies visited them and their tendency of issuing prescriptions consisted of these generic drugs that were in this drug group and included on the drug reimbursement list. These doctors said the tendency of drug consumption of patients in the district was significantly high and they found it difficult to resist them in this aspect. They displayed a bilateral attitude regarding the effects of the drugs. While some of the doctors said they would not interfere in scientific approval, some preferred the original drug form rather than generic drugs. In this sense, it was determined that there was disagreement regarding generic drugs.